2011
DOI: 10.1002/ps.2301
|View full text |Cite
|
Sign up to set email alerts
|

Validation of RNA interference in western corn rootworm Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) adults

Abstract: This research clearly demonstrates the effect of RNAi on WCR adults that have been exposed to dsRNA by feeding and establishes a tool to screen dsRNAs of potential target genes in adults. This technique may serve as an alternative to target screening of larvae which are difficult to maintain on artificial diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 33 publications
2
94
0
2
Order By: Relevance
“…At the end of each PCR reaction, a melting curve was generated to confirm single peaks and rule out the possibility of primer-dimer and nonspecific product formation. Relative quantification of the transcripts were calculated using the comparative 2°ΔΔCq method (Livak and Schmittgen, 2001) and were normalized to b-actin (Rangasamy and Siegfried, 2012).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of each PCR reaction, a melting curve was generated to confirm single peaks and rule out the possibility of primer-dimer and nonspecific product formation. Relative quantification of the transcripts were calculated using the comparative 2°ΔΔCq method (Livak and Schmittgen, 2001) and were normalized to b-actin (Rangasamy and Siegfried, 2012).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…The development of RNA interference (RNAi) technology for the control of WCR via transgenic expression of long double-stranded RNA (dsRNA) in maize provides an additional MOA againstWCR (Baum et al, 2007). Previous experiments have shown that RNAi is also effective against adult rootworms (Rangasamy and Siegfried, 2012). Oral sensitivity of adults to RNAi provides an additional option to suppress populations by reducing egg viability.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the authors also demonstrated that corn plants expressing dsRNA directed against the v-ATPase A gene effectively protected the plants from root damage, documenting for the first time the potential for in planta RNAi as a possible pest management tool. Rangasamy and Siegfried (2012) designed dsRNA for the same v-ATPase described by Baum et al (2007) and documented that oral delivery to adult rootworms could also induce reduced gene expression and protein synthesis and that mortality in the exposed beetles could be achieved within 14 days. The authors suggest that adults may provide a more effective developmental stage to screen for activity of dsRNAs because they are easier to manipulate and can be induced to feed compulsively on artificial diet by incorporating a natural feeding stimulant.…”
Section: Introductionmentioning
confidence: 99%
“…이러한 약제저항성 문제로 인해 미생물농약, 천적, 식물 essential oil, 곤충병원성 곰팡이 등과 같은 생물적 방제방 어 왔지만 (Mutti et al, 2006;Rangasamy and Siegfried, 2012;Sapountzis et al, 2014;Wynant et al, 2014), 위의 두 적용방법 모두 해충방제에 직접 적용하기에 무리가 있 는 방법들이다. 이러한 문제로 인해 최근에는 방제대상 곤 충의 dsRNA를 발현시키는 transgenic plant에 대한 연구가 이루어지고 있다 (Bhatia et al, 2012;Mao et al, 2007).…”
Section: 서 론unclassified